Impact of a sensory stimulation program conducted by family members on the consciousness and pain levels of ICU patients: A mixed method study - Adineh, Mohammad; Elahi, Nasrin; Molavynejad, Shahram; Jahani, Simin; Savaie, Mohsen (Frontiers in Medicine, 2022)
Background The results of several studies show the different effects of a balanced sensory stimulation program (SSP) on patients with brain injury admitted to the intensive care unit (ICU), but these effects have been less studied based on mixed and comprehensive methods. Method This mixed-method study involved 66 patients with brain injury admitted to the ICU who were allocated into intervention (n = 33) and control (n = 33) groups using random stratified sampling. Patients in the intervention group received a sensory stimulation program from family members for 1 h daily during ICU hospitalization, while the control group received only routine care. Patients' level of consciousness and pain intensity were measured immediately before and after the intervention using Glasgow Coma Scale (GCS) and Behavioral Pain Scale (BPS), respectively. In-depth unstructured interviews were conducted with the patients in the intervention group 3 months after discharge from the ICU. These interviews were analyzed following Graneheim and Lundman (2004) conventional content analysis method. Results A significant difference was found between the study groups in terms of the mean difference of GCS (P =0.001) and BPS score (P = 0.001) before and after intervention. Patients in the intervention group had a higher mean GCS and a lower mean BPS than did patients in the control group. The main themes extracted from the qualitative analysis confirmed the results obtained from the quantitative phase of the study. Conclusion The combination of the quantitative and qualitative findings suggested that amidst the many hardships and sufferings brain injury patients go through in the ICU, a sensory stimulation program offered by family members may have many benefits such as increased level of consciousness and reduced pain for these patients. Therefore, it is necessary to formulate a framework for this program and provide the needed facilities in order to benefit more from the capacity of such programs for ICU patients.